Nonclassical Monocytes Are Prone to Migrate Into Tumor in Diffuse Large B-Cell Lymphoma - Le Gallou, Simon; Lhomme, Faustine; Irish, Jonathan M.; Mingam, Anna; Pangault, Celine; Monvoisin, Celine; Ferrant, Juliette; Azzaoui, Imane; Rossille, Delphine; Bouabdallah, Krimo; Damaj, Gandhi; Cartron, Guillaume; et al. (Frontiers in Immunology, 2021)
Absolute count of circulating monocytes has been proposed as an independent prognostic factor in diffuse large B-cell lymphoma (DLBCL). However, monocyte nomenclature includes various subsets with pro-, anti-inflammatory, or suppressive functions, and their clinical relevance in DLBCL has been poorly explored. Herein, we broadly assessed circulating monocyte heterogeneity in 91 DLBCL patients. Classical- (cMO, CD14pos CD16neg) and intermediate- (iMO, CD14pos CD16pos) monocytes accumulated in DLBCL peripheral blood and exhibited an inflammatory phenotype. On the opposite, nonclassical monocytes (ncMOSlanpos, CD14low CD16pos Slanneg and ncMOSlanneg, CD14low CD16pos, Slanneg) were decreased in peripheral blood. Tumor-conditioned monocytes presented similarities with ncMO phenotype from DLBCL and were prone to migrate in response to CCL5 and CXCL12, and presented similarities with DLBCL-infiltrated myeloid cells, as defined by mass cytometry. Finally, we demonstrated the adverse value of an accumulation of nonclassical monocytes in 2 independent cohorts of DLBCL.